Achieving the SDGs: Challenges and Solutions for MSMEs Against Predatory Digital Loans - Febrian, Silvia Jultikasari (Jurnal Indonesia Sosial Sains, 2024)
Predatory digital lending poses significant challenges to the sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. This study explores the reasons, consequences, and impacts of predatory digital loans on MSMEs, focusing on how these practices hinder economic well-being and growth. The research employs a qualitative method, utilizing content analysis from secondary sources, including academic journals, reports, and government documents. Data were collected through an in-depth review of literature and case studies of MSMEs affected by predatory loans. The findings reveal that many MSMEs, particularly in rural areas, lack sufficient financial literacy, which increases their vulnerability to predatory lending. Legal frameworks, such as POJK 35/POJK.05/2018, are inadequate in regulating debt collection ethics, allowing illegal practices to flourish. Additionally, gender disparities affect loan approval rates, with female borrowers facing higher risks of harassment. The study concludes that improving financial literacy, strengthening government regulations, and fostering collaboration between MSMEs, government bodies, and financial institutions are essential for protecting MSMEs from predatory digital lending. By doing so, MSMEs can achieve sustainable growth and contribute more effectively to Indonesia's economic development and the achievement of the Sustainable Development Goals (SDGs).